The role of money; what it should be, contrasted with what it has become - Soddy, Frederick, 1877-1956 (London, G. Routledge and Sons, Ltd., 1934)
The book attempts to clear up the mystery of money in its social aspect. It shows what money is, what it does and what it should do.
Includes bibliographical references (p. 221-222.)
oif 22/07/14
Loan
Keywords: Money; Currency question